Dual effect of wood fiber as bio-nucleating agent and reinforcement material in wood fiber/poly(lactic acid) composites - Chao Lv; Shupin Luo; Wenjing Guo (eXPRESS Polymer Letters)
Biodegradable plastics such as poly(lactic acid) (PLA) are gaining considerable interest as promising substitutes for conventional petroleum-based plastics due to ecological, health, and environmental concerns. PLA possesses good biodegradability and biocompatibility but is limited by its slow crystallization rate, low impact resistance, and high costs. In this study, a small amount of natural wood fiber (WF) was incorporated into PLA to improve mechanical and crystallization properties as well as cost reduction. The effects of WF size (20–40, 80–100, and 140–160 mesh) and loading content (0.5–8 wt%) on the mechanical and crystallization properties were investigated and compared. Results indicated that WF of 80–100 mesh (WF80-100) exhibited a better reinforcement effect on PLA than the other two sizes of WF. The optimal loading content for WF80-100 was 1 wt%, at which the flexural and tensile strength increased by about 18% compared to neat PLA, and the elongation at break increased by 27%. Moreover, the degree of crystallinity and crystallization rate significantly increased with the addition of WF80-100. Polarized optical microscopy observation revealed that the number of spherulites increased in 1WF80-100/PLA composite and the spherulite size decreased compared to neat PLA. These findings confirmed that WF, even at a low addition level, could act as both a reinforcement material and an efficient nucleating agent for PLA, which is closely related to its size.